2010
DOI: 10.1007/s10453-010-9178-7
|View full text |Cite
|
Sign up to set email alerts
|

(1 → 3)-β-d-glucan in different background environments and seasons

Abstract: This study was undertaken to investigate how the length of the extraction period influences the (1 ? 3)-b-D-glucan (b-glucan) yield and also to examine the background concentration of b-glucan as airborne b-glucan in outdoor environments in different seasons and as concentrations in airborne and floor dust in offices. To ensure compatibility between results obtained in different laboratories, it is important to use optimal and standardised methods to extract and quantify b-glucan. In this study, an extraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
68
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 36 publications
10
68
2
1
Order By: Relevance
“…In Danish towns and upwind of industrial areas, inhalable (i.e. particles with aerodynamic diameter \100 lm) endotoxin concentrations were shown to be \10 EU m -3 throughout the year (Madsen 2006). While most of our upwind concentrations fall close to values reported by other researchers, it is possible that some of the elevated background concentrations are a result of assessing total airborne endotoxin instead of inhalable and respirable particles (discussion to follow).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…In Danish towns and upwind of industrial areas, inhalable (i.e. particles with aerodynamic diameter \100 lm) endotoxin concentrations were shown to be \10 EU m -3 throughout the year (Madsen 2006). While most of our upwind concentrations fall close to values reported by other researchers, it is possible that some of the elevated background concentrations are a result of assessing total airborne endotoxin instead of inhalable and respirable particles (discussion to follow).…”
Section: Resultssupporting
confidence: 74%
“…In background ambient environments, inhalable, thoracic, and respirable endotoxin concentrations are generally \10 endotoxin units (EU) m -3 (Heinrich et al 2003;Mueller-Anneling et al 2004;Madsen 2006). However, exposure to relatively low ambient concentrations of 50-100 EU m -3 has been shown to cause respiratory effects (Castellan et al 1987;Milton et al 1996;Zock et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Probably this was the reason for the insignificant relationship between air contaminants and wheezing or allergen sensitization reported by them. Radon et al, 9 Monsó et al, 8 found 2.8EU/m 3 median endotoxin level in the greenhouses (data from ng are converted to EU) of Spain; however, Madsen 12 found much higher endotoxin level (median=13.2EU/m 3 ) in the greenhouses of Denmark. This observation supports our assumption that bioaerosol exposure conditions in different countries can be different and strengthens the need for an independent extensive study in the greenhouses of the Midwest US.…”
Section: Bioaerosol Exposures To Greenhouse Workersmentioning
confidence: 97%
“…This observation supports our assumption that bioaerosol exposure conditions in different countries can be different and strengthens the need for an independent extensive study in the greenhouses of the Midwest US. Use of an inhalable sampler by Madsen 12 an advancement of the methodology compared to previous researchers and we will follow this sampling method in this proposed study. Recent studies from Denmark showed that personal exposure to fungi in greenhouses ranged between 1.8×102 and 3.4×106 CFU/ m3 and to bacteria between 1.6×10 1 and 4.2×10 5 CFU/m 3 .…”
Section: Bioaerosol Exposures To Greenhouse Workersmentioning
confidence: 99%
“…Although bacterial communities and endotoxin concentrations have been reported in several studies (Gorny and Dutkiewicz 2002;Park et al, 2002;Herr et al, 2003;Oppliger et al, 2005;Rusca et al, 2008;Tendal and Madsen, 2011), only a few studies have evaluated their relationships with the types of land use (Mueller-Anneling et al, 2004;Madsen, 2006;Bowers et al, 2010;Tager et al, 2010;Woo et al, 2013). In a study designed to investigate the risk factors of childhood asthma, air samples were collected from several locations throughout Fresno, a city in central California, USA; the study revealed that the endotoxin concentrations varied among various geographical regions.…”
Section: Introductionmentioning
confidence: 99%